Bioactive potential of Cyanobium sp. pigment-rich extracts - Pagels, F. (2020)
Cyanobacteria are able to synthesize high-value compounds, such as pigments, known for their bioactivities and several industrial uses. One of the key points for the extraction of pigments is solvent selection. Solvent interferes on pigments concentration, thus affecting the bioactive potential of the extracts. In this work, using frozen-dried biomass of Cyanobium sp. LEGE 06113, organic and aqueous pigment-rich extracts were obtained by a classic extraction methodology using four solvents — acetone (A), ethyl acetate (EA), ethanol (E) and water (W). In order to increase the efficiency of extraction from the cyanobacterium biomass, successive extractions were performed by using water after organic extraction (A-W, E-W, EA-W) and acetone after the aqueous extraction (W-A). Extraction yield and profile of carotenoids, phycobiliproteins, and phenolic compounds were quantified. The bioactive potential of Cyanobium sp. extracts was assessed in terms of antioxidant capacity (ABTS•+, •NO, O2•− scavenging), anti-inflammatory capacity (COX inhibition), and cytotoxicity (HepG2). W-A showed the higher antioxidant capacity and higher content in carotenoids. E-W showed the highest content in phycobiliproteins and great antioxidant capacity. In terms of anti-inflammatory capacity, 100 μgE mL−1 of E-W extract exhibited capacity to inhibit both COX-1 and COX-2 enzymes. Finally, in what concerns the cytotoxic evaluation, E, W, A-W, E-W, and EA-W revealed to have no cytotoxic effects in concentrations up to 750 μgE mL−1. Overall, this work constitutes a valid contribution for the valorisation of Cyanobium sp. pigment-rich extracts for biotechnological applications.